Edge Intelligence in Private Mobile Networks for Next-Generation Railway Systems - Asad, Syed Muhammad; Tahir, Ahsen; Rais, Rao Naveed Bin; Ansari, Shuja; Abubakar, Attai Ibrahim; Hussain, Sajjad; Abbasi, Qammer H.; Imran, Muhammad Ali (Frontiers in Communications and Networks, 2021)
The integration of Private Mobile Networks (PMN) with edge intelligence is expected to play an instrumental role in realizing the next generation of industry applications. This combination collectively termed as Intelligent Private Networks (IPN) deployed within the scope of specific industries such as transport systems can unlock several use-cases and critical applications that in turn can address rising business demands. This article presents a conceptual IPN that hosts intelligence at the network edge employing emerging technologies that satisfy a number of Next Generation Railway System (NGRS) applications. NGRS use-cases along with their applications and respective beyond 5G (B5G) enabling technologies have been discussed along with possible future research and development directions that will allow these promising technologies to be used and implemented widely.